A Critical Assessment of the Evidence for Low-Level Laser Therapy in the Treatment of Hair Loss. Issue 2 (February 2017) - Gupta, Aditya K.; Foley, Kelly A.
Abstract : BACKGROUND: Low-level laser therapy (LLLT) is currently in use to stimulate hair growth and is quickly gaining in popularity due to the ease of use and absence of side effects. In 2015 alone, the number of LLLT devices with the Food and Drug Administration clearance has doubled. OBJECTIVE: To consolidate evidence and establish which data are still required for the widespread acceptance of LLLT for hair loss therapy. METHODS AND MATERIALS: A thorough search of the PubMed database was conducted to obtain studies investigating LLLT for androgenetic alopecia in men and women. RESULTS: Nine trials were identified for comb and helmet/cap devices, five of which were randomized controlled trials. Data comparison across LLLT trials and with traditional hair loss therapy (minoxidil, finasteride) was not straight forward because there was a lack of visual evidence, sample sizes were low, and there were large variations in study duration and efficacy measurements. CONCLUSION: There are a number of unanswered questions about the optimum treatment regimen, including maintenance treatment and the long-term consequences of LLLT use. Moving forward, protocols should be standardized across trials. Moreover, it is recommended that future trials include visual evidence and trial duration be expanded to 12 months.